2010
DOI: 10.1353/hpu.0.0361
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Consumption Practices and Cancer Risk in African Americans in the Rural South

Abstract: This study describes the dietary consumption practices of a sample of African Americans in the rural South. A qualitative research design involving a cross-sectional food diary was utilized. Complete datasets were collected from 114 participants, 66% female, between the ages of 19 and 79 years. The consumption of a variety of fruits, non-starchy vegetables and unprocessed cereals in daily meals was low in this sample. Frequent consumption of fried foods; fast foods; sugary, carbonated beverages; processed, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…Low-income individuals are less likely to meet dietary guidelines, and adherence to dietary recommendations is lower in AAs [38]. Studies also show that AAs prefer different foods than EAs [39], and dairy consumption is lower in AAs than other ethnic groups [40, 41]. Along with low dietary supplement usage, these factors partly contributed to lower calcium and vitamin D intake in our study participants.…”
Section: Discussionmentioning
confidence: 88%
“…Low-income individuals are less likely to meet dietary guidelines, and adherence to dietary recommendations is lower in AAs [38]. Studies also show that AAs prefer different foods than EAs [39], and dairy consumption is lower in AAs than other ethnic groups [40, 41]. Along with low dietary supplement usage, these factors partly contributed to lower calcium and vitamin D intake in our study participants.…”
Section: Discussionmentioning
confidence: 88%
“…2,3 Recent studies suggest that obesity is also more prevalent in rural children and adolescents than their urban counterparts. [4][5][6] Davis et al reported that in the 2003-2006 National Health and Nutrition examination survey (NHANes) the prevalence of obesity in 2-to 18-year-olds was about 5% higher in rural compared to urban children (21.8% vs. 16.9%). 6 if residing in rural areas is associated with a greater risk of obesity in children, then a better understanding of why children are more likely to become obese in rural areas is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…in addition, their intake of fruits and nonstarchy vegetables is low. 16 Disproportionately more rural adults are physically inactive compared to their urban peers (62.8% vs. 59.3%). 2 A solid body of research demonstrates that risky behaviors such as sexual activity, weapon carrying, and tobacco, alcohol, and substance use, 17 increase during adolescence, and rural adolescents are at greater risk than urban adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research regarding dietary fat intake, which included Black participants, has been descriptive and focused on the quantity of dietary fat consumed, dietary patterns, and some demographic variables (Bovell-Benjamin, Dawkins, Pace, & Shikany, 2010;Brown et al, 2010;Bruening, Gilbride, Passannante, & McClowry, 1999;Coates et al, 1995;Deshmuk-Taskar, Nicklas, Yang, & Berenson, 2007;DeshmukhTaskar et al, 2009;Fitzgibbon et al, 2005;Fitzgibbon et al, 2008;Gans et al, 2009;James, 2009;Laroche, Wallace, Snetselaar, Hillis, & Steffen, 2012;Lewis et al, 2003;Nicklas, Farris, Myers, & Berenson, 1995;Nicklas, Myers, Reger, Beech, & Berenson, 1998;Sharma et al, 2009;Sijtsma et al, 2012;Winkleby, Robinson, Sundquist, & Kraemer, 1999). Researchers have also examined dietary fat intake in relation to other health problems (e.g., diabetes, cancer, and obesity) (Bortsov et al, 2011;Crump et al, 2006;Lagou et al, 2011).…”
Section: Background and Significancementioning
confidence: 99%